ANALYSIS OF FOOD INTAKE PARENTS AND CHILDREN FRESHMAN IN A PROGRAM MULTIPROFESSIONAL TREATMENT OF OBESITY. (Fiep Bulletin - online, 2013)
Excess weight and obesity are considered health problems worldwide, which have increased mainly in urban areas of countries with medium and low incomes. One of the important factors related to childhood obesity is the family influence and their eating habits. Since there is a relationship between eating habits of children and adults from the same family, the aim of this study was to evaluate the nutritional composition of macro and micronutrients power of parents and children and their possible associations regarding dietary deficiencies and excesses. We evaluated twenty-four individuals members of a multidisciplinary program for the treatment of obesity with 11 parents of teens participating in the program, entering the second half of the year 2012. For analysis of eating habits was applied a food record of 24 hours held for seven consecutive days in the first week of intervention in both groups (parents and children). In the results, we observe that the median BMI obtained is characteristic of overweight and body fat percentage is above the range considered healthy. When comparing the caloric value of the food of teenagers and their parents, there was significant difference between them, and the amounts consumed by older adolescents. Regarding the adequacy of macronutrients, both feeding the teenagers as the responsible adequacy proposal presented by the DRIs related to percentage. Regarding the consumption of micronutrients, it can be seen that most of the vitamins and minerals are below the established recommendation for daily consumption. Thus, the presence of a multidisciplinary team to monitor and guide teens and their parents shows their importance to modify and improve eating habits in an attempt to minimize possible damage to health caused by excess body weight and poor nutrition.
Keywords: Obesity; Teens; Food Record; Intervention